Data-driven assessment of Apulian road network resilience: Bridge unavailability and inner municipality isolation impact - Niloofar Kheirkhahan; Loredana Bellantuono; Nicola Amoroso; Roberto Cilli; Lorenzo De Biase; Valentina Lucaferri; Alfonso Monaco; Chiara Ormando; Ester Pantaleo; Domenico Pomarico; Sabina Tangaro; Alberto Tofani; et al. (PLoS ONE, 2025)
Road networks are crucial for the movement of resources, passenger transportation, and supply chains. In seismically active areas like Italy, earthquakes can compromise road infrastructure, leading to structural failures and connectivity disruptions. Bridges, vital for travel and emergency response, are especially vulnerable to these extreme events, making their maintenance and recovery crucial for preserving transport efficiency. This study examines the resilience of the Apulian road network against bridge failures by assessing seismic hazards, the structural vulnerability of each bridge to seismic actions, and the systemic consequences of its disruption. A bridge criticality score is defined to support data-driven decision-making for bridge maintenance and recovery. This novel quantitative metric integrates seismic hazard data at each bridge site, fragility curves, and topological complex network analysis to provide a comprehensive evaluation of bridge criticality. Additionally, the risk of isolation for inner municipalities due to bridge disruptions is assessed using centrality metrics. By combining the bridge criticality score with an emphasis on inner municipalities, this approach offers valuable insights to improve road network resilience, mitigate isolation risks, and promote territorial sustainability in earthquake-prone zones.